2019
DOI: 10.1002/ecy.2612
|View full text |Cite
|
Sign up to set email alerts
|

Multiple temperature effects on phenology and body size in wild butterflies predict a complex response to climate change

Abstract: Citation: Davies, W. J. 2019. Multiple temperature effects on phenology and body size in wild butterflies predict a complex response to climate change. Ecology 100(4):Abstract. Temperature-induced alterations in phenology and body size are the cumulative outcome of sequential effects impacting development and are universal responses to climate change. Most studies have so far focused on phenological responses to warming in multiple taxa across space and time, or the ontogenetic effects of temperature in the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 34 publications
(109 reference statements)
6
26
1
Order By: Relevance
“…This may also be the reason for the decrease in adult size when higher temperatures occur during the pupal stage, because the pupa of this species also produces secretions and sounds to attract ants (Thomas & Lewington, 2014). This contrasts with results in a study of the univoltine butterfly Anthocharis cardamines, which is not associated with ants in the larval or pupal stages, which found that an increase in adult body size was correlated with temperature increases during the pupal stage of development, and that both sexes responded in the same way (Davies, 2019).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This may also be the reason for the decrease in adult size when higher temperatures occur during the pupal stage, because the pupa of this species also produces secretions and sounds to attract ants (Thomas & Lewington, 2014). This contrasts with results in a study of the univoltine butterfly Anthocharis cardamines, which is not associated with ants in the larval or pupal stages, which found that an increase in adult body size was correlated with temperature increases during the pupal stage of development, and that both sexes responded in the same way (Davies, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…Polyommatus bellargus , for example, overwinters as a larvae whereas P. argus and P. coridon overwinter as eggs (Thomas & Lewington, ). Yet, they are all direct developers (i.e., there is no pupal diapause) and therefore may be subject to more seasonal time constraints and variation than species which diapause in the pupal phase, such as A. cardamines (Davies, ). This may explain why all three lycaenid species we have studied, and H. comma , respond to temperature in the larval stage (Table ; Fenberg et al, ) but the pierid butterfly A. cardamines , which overwinters in the pupal stage, instead responds to temperature in the pupal stage (Davies, ).…”
Section: Discussionmentioning
confidence: 99%
“…has shown the effects of temperature during three time-windows on emergence dates (Davies, 2019). However, our results are consistent with evidence for larger effects of temperature on later immature stages in Lepidoptera (e.g.…”
Section: Environmental Determinants Of Phenologysupporting
confidence: 91%
“…Roy et al., 2015). We cannot rule out the possibility of temperature effects on phenology at other times of the year because our statistical technique was limited to one time‐window per model, and recent research on a population of one of the focal species ( A. cardamines ) has shown the effects of temperature during three time‐windows on emergence dates (Davies, 2019). However, our results are consistent with evidence for larger effects of temperature on later immature stages in Lepidoptera (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, studying changes in their phenology and abundance is a prerequisite to understanding ecosystem responses to environmental changes. Changes in phenology and abundance in response to environmental changes vary with species and spatial scale (Bell et al, 2018;Frik et al, 2020), and generalisation has proved elusive (Diez et al, 2012;Davies, 2019).…”
Section: Introductionmentioning
confidence: 99%